Selective Syntheses of Coumarin and Benzofuran Derivatives Using Phenols and α-Methoxy-β-ketoesters - Miyata, Ryo; Shigeta, Takashi; Kumazawa, Shigenori; Egi, Masahiro (SynOpen, 2023)
Selective syntheses of coumarin and benzofuran derivatives were achieved via HClO4-mediated intermolecular annulation using phenols and α-methoxy-β-ketoesters. Coumarins are formed under dehydrated conditions, whereas benzofurans are formed in the presence of water. In the synthetic process of benzofurans, α-methoxy-β-ketoesters are converted into α-methoxyacetophenones, and the methoxy group is an important element in the intermolecular annulation.
Keywords: coumarin; benzofuran; selective syntheses; phenol; α-methoxy-β-ketoester; α-methoxyacetophenone